The gender binary, the third space, and public university washrooms - Fraser, Johanna (My University, 2016)
Sexed bathrooms are key locations for sex and gender violence and oppression. Recent political events have made the problem of gendered bathrooms in public spaces much more visible. This project aims to address this issue in part as an iteration of the ways that gender and sex can be critiqued and practiced. It presents and critiques the problem of the gender binary from two perspectives—the feminist, and the feminist poststructuralist—and argues that Homi Bhabha’s third space approach to constructing identity offers us a unique way of critiquing the gender binary while keeping in mind the discursiveness, and fluidity of gender, but also the fundamentality to which many people ascribe their own gender identity. As a demonstration of the way the third space can address the problem of the gender binary this project contextualizes the third space by applying it to gender neutral washrooms. It will also offer case studies of two Canadian universities—Queen’s and Victoria—who have put gender neutral washrooms in place on their campuses.